PANDANGAN DUNIA NATSUME SOSEKI DALAM NOVEL SANSHIRO: SEBUAH KAJIAN SOSIOLOGISASTRA (World View ofNatsume Soseki in Sanshiro: A Study of Sociology of Literature) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
This research observes the social problems of theO Meiji period (1868-1912 )as the impact of the westernization as presented in Natsume Soseki's novel Sanshiro. It also dealt with the attitude's of the literature circle voiced by Natsume Soseki as response towards the social problem's which hap¬pened in the period. In this reseach, the theory Genetic Structuralism developed by Lucien Goldmann was employed, since this theory was able to gain the total signifi¬cance which was expected. According to the theory, the author created in his literary work figure's and imagined objects as reflection of his world view. The subject matter that the author expressed in his work could be understood only as integral part of the author's life and motives and the society as a whole. Therefore, this research also focussed on not only the structure of the texts but also the social structure which became its setting. The result showes that the virgorous process of westernization of Japan especially during two decades of the Meiji period had caused the Japanese to lose their identity. At the time, a westernized social circle emerged, who glo¬rified individual freedom, pragmatism, egoism, and hedonism. Natsume Soseki, who was born and raised in that kind of social condition, felt the calling to contribute his ideas to solve these social problems. In the novel Sanshiro, Soseki's frame of thought was well known as the " integration of three worlds" which suggested that the Japanese should develop on her own identity. Soseki was not anti-West, he suggested that the Japanese should absorb the positive western values, such as values which empowered individualy, and then should combine it with indigineous values in a syn¬ergy. Further, he suggested that the Japanese should always learn enthusiatically to develop sciences and tecnology, so that later on they could participate in the global world.